Critical Thinking and Academic Performance in final cycle students at FIEECS-UNI - Macedo Dávila, Antonieta (2023)
The present research had the objective of determining the relationship between critical thinking and academic performance in the students of the last cycle 2021-2 of the FIEECS of the National University of Engineering. The research methodology has a quantitative approach, the type is correlational with a non-experimental cross-sectional design. To determine the variables, the Watson-Glaser (1980) was use for the students' critical thinking variable and for the academic performance variable, the weighted average of the students was used. Concerning the correlation between critical thinking and academic performance, a Spearman's correlation coefficient of 0.249 was obtained, which indicates a weak and positive correlation, for a p-value =.027 <.05, rejecting the null hypothesis (Ho), which shows, with a confidence level of 95%, that there is a significant relationship between Critical Thinking and Academic Performance in the ninth and tenth year students of the 2022-1 academic cycle at the FIEECS. With respect to the dimensions of the critical thinking construct, high percentages were obtained except in the Inference dimension with 54.4%.